Planck residuals anomaly as a fingerprint of alternative scenarios to inflation - Domènech Fuertes, Guillem; Chen, Xingang; Kamionkowski, Marc; Leyb, Avraham (Journal of cosmology and astroparticle physics, 2020)
Planck's residuals of the CMB temperature power spectrum present a curious oscillatory shape that resembles an extra smoothing effect of lensing and is the source of the lensing anomaly. The smoothing effect of lensing to the CMB temperature power spectrum is, to some extent, degenerate with oscillatory modulations of the primordial power spectrum, in particular if the frequency is close to that of the acoustic peaks. We consider the possibility that the lensing anomaly reported by the latest Planck 2018 results may be hinting at an oscillatory modulation generated by a massive scalar field during an alternative scenario to inflation or by a sharp feature during inflation. We use the full TTTEEE+low E CMB likelihood from Planck to derive constraints on these two types of models. We obtain that in both cases the AL anomaly is mildly reduced to slightly less than 2σ, to be compared with the 2.8σ deviation from AL=1 in ΛCDM. Although the oscillatory features are not able to satisfactorily ease the lensing anomaly, we find that the oscillatory modulation generated during an alternative scenario alone, i.e. with AL=1, presents the lowest value of χ2, with Δχ2=−13 compared to ΛCDM. Furthermore, the Akaike Information Criterion suggests that such an oscillation constitutes an attractive candidate since it has a value ΔAIC=−5 with respect to ΛCDM, comparable to the AL parameter. We also obtain that the equation of state parameter in the alternative scenario is given at 1σ by w=0.13±0.17. Interestingly, the matter bounce and radiation bounce scenarios are compatible with our results. We discuss how these models of oscillatory features can be tested with future observations.
Gesehen am 23.12.2020